التنمر المدرسي وعلاقته بالمهارات الاجتماعية لدى عينة من تلاميذ المرحلة المتوسطة دراسة ميدانية بمؤسسة 17أكتوبر 1961بالأغواط - غياثي حنان; داودي حسناء; جخدم فتيحة (My University, 2023)
School bullying is one of the behavioral problems that have become a danger in the school environment, as it has different forms and images, whether psychological, physical, verbal, social or electronic, that have negative effects, whether on the viewer or the victim of bullying and the sensitivity of the subject. This study came to investigate the relationship between school bullying And the social skills of third-year students are average, and to verify this, a sample of 49 students (male and female) was relied upon, and in order to collect data, two tools were relied upon: school bullying and social skills, which were built by the two students after reviewing many studies on the subject. Relying on the descriptive approach that is commensurate with the study and data processing, the SPSS 22 program was relied upon to analyze the results, the results of which showed towards achieving the following -The level of school bullying among third-year students in intermediate education (average). -The level of social skills among third-year students in the middle school stage (low). -There are no statistically significant differences in school bullying among third-year students in the intermediate education stage. -There are no statistically significant differences in the social skills of the third year students in the intermediate education stage. Keywords: school bullying, social skills, intermediate educatio